Menghubungkan Nilai-Nilai Edukatif Bermuatan 4C Melalui Game Online Mobile Legends pada Anak - Aji, Priyo Kartiko; Purnamasari, Iin; Arisyanto, Prasena (CV. Supernova Office Stationary and Printing, 2023)
The background of this research is the advancement of sophisticated technology to present a game in an internet network (online game). Currently online games have entered the world of children, this can be seen from the rise of elementary school students who use online games. The activity of playing online games certainly has its own impact on its users. This type of research is descriptive qualitative, data collection techniques using interviews, questionnaires and documentation. The research data was obtained through research subjects consisting of teachers, students and parents. The results of the study show that most elementary school students in Kampung Widuri experience a tendency to play mobile legends online games. In playing online games, there is an impact of 4C content on elementary school students in Widuri Village. Where there are more negative impacts than positive impacts. The positive impact is that students can be experienced and have skills in the field of technology, can make good cooperation strategies in a team and can be used as entertainment for students. While the negative impact is that the students' emotional level increases and is difficult to control, students lose track of time, students like to ask for money for online mobile legends games, students don't care about their surroundings, interfere with student health, and students become lazy and often ignore other important activities.